السياسة العقابية للمشرع السوري في الجرائم الإرهابية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Our study centered on the punitive policy of the Syrian legislator in terrorist crimes, which is included in the Anti-Terrorism Law No. 19 of 2012 and Law No. 20 of 2012, through the examination of the general penal rules stipulated by the legislator in terrorist crimes, An analysis of the general proportionality between terrorist crimes on the one hand and the penalties imposed on them on the other. It also discusses the role of the discretionary power of the judge in imposing and applying the punishment, analyzing the legislator's plan to grant legal and mitigating legal excuses. And we also examined the comprehensive penal supporters, punishments or measures for terrorist crimes, by talking about each of the forfeiture provisions in terrorist crimes, the resolution of associations and organizations that initiate an act of terrorism, and layoffs, workers and denial of financial rights arising from the job when they are proven to have committed a crime of terrorist crimes. تمحورت دراستنا ضمن هذا البحث حول السياسة العقابية للمشرع السوري في الجرائم الإرهابية، والتي تضمنها قانون مكافحة الإرهاب رقم 19 لعام 2012، والقانون رقم 20 لعام 2012، وذلك من خلال البحث في قواعد الجزاء العامة التي نص عليها المشرع في جرائم الإرهاب، وما تضمنه ذلك من تحليل لمدى التناسب العام بين الجرائم الإرهابية من جهة، وبين العقوبات المقررة لها من جهة أخرى، والحديث عن دور السلطة التقديرية للقاضي في فرض وتطبيق العقوبة، وتحليل خطة المشرع في منح الأعذار القانونية المحلّة والمخففة، كما تناول البحث أيضاً دراسة المؤيدات الجزائية الشاملة التي نص عليها المشرع كعقوبات أو تدابير للجرائم الإرهابية، من خلال الحديث عن كل من أحكام المصادرة في الجرائم الإرهابية، وحل الجمعيات والمنظمات التي تباشر عملاً إرهابياً، وتسريح الموظفين والعمال والحرمان من حقوقهم المالية الناشئة عن الوظيفة متى ثبت ارتكابهم لجريمة من الجرائم الإرهابية.